Prototype Smart Home Dengan Konsep Internet Of Things Menggunakan Arduino - Erlan Bahtiar; Budi Darmawan; Syafaruddin Ch; Sabar Nababan (Depertment of Electrical Engineering University of Mataram, 2023)
Smart Home is a residence or dwelling where electrical appliances are connected to a communication network for control, monitoring, or remote access. One of the technologies used in creating a smart home is the Internet of Things (IoT). In this research, a prototype of a smart home was designed using the DHT11 Sensor and RFID (Radio Frequency Identification) Sensor. The controlled appliances include lights, fans, and a door lock. In the design of this IoT-based smart home, the results showed that the Internet of Things system functions optimally on the controlled hardware. The switching relay works well, where when the status in the application is ON, the lights will turn on, while when the status is OFF, the lights will turn off. In the automation of the DHT11 Sensor, when the room temperature exceeds 30°C, the fan will turn on, whereas if the room temperature is below 30°C, the fan will turn off. And in the automation of the RFID-RC522 Sensor, when a registered tag card is placed on the RFID reader, the door lock will open, but if an unregistered tag card is placed on the RFID reader, the door lock will remain locked.